2019
DOI: 10.1002/ejic.201900810
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Conjugation of Transition Organometallic Complexes to Peptides and Proteins: Strategies and Applications

Abstract: The advent of bioorthogonal chemistry has revolutionized the common practices in protein bioconjugation and contributed to a large extent to the development of chemical biology, a discipline aimed at studying biological/biochemical processes/events in their natural setting (living cells, whole organisms) using dedicated chemical tools. This minireview in- IntroductionWithin the last two decades or so, protein bioconjugation methods have undergone a dramatic evolution as the concept of [a] 26 Scheme 13. On-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…Although solid phase peptide synthesis (SPPS) and solid phase organic chemistry (SPOC) are methods of choice for the preparation of peptides and peptide conjugates, in most of the cases, the formation of coordination compounds occurs in the solution, facilitating the monitoring of the complex formation and analysis of final products, including advanced fluorescence studies of some bidentate chemosensors based on the benzoxazol-5-yl-alanine (Figure 9C) [151,152]. For special purposes, the attachment of an already formed complex motif to the peptide assembled on solid support could be performed or the reaction with metal ions carried out with an immobilized peptide [153]. There are reports that the presence of metal complex may cause side reactions, including the non-standard cleavage of the Rink amide linker [154].…”
Section: Immobilized Heterocyclic Peptide Conjugates As Ligandsmentioning
confidence: 99%
“…Although solid phase peptide synthesis (SPPS) and solid phase organic chemistry (SPOC) are methods of choice for the preparation of peptides and peptide conjugates, in most of the cases, the formation of coordination compounds occurs in the solution, facilitating the monitoring of the complex formation and analysis of final products, including advanced fluorescence studies of some bidentate chemosensors based on the benzoxazol-5-yl-alanine (Figure 9C) [151,152]. For special purposes, the attachment of an already formed complex motif to the peptide assembled on solid support could be performed or the reaction with metal ions carried out with an immobilized peptide [153]. There are reports that the presence of metal complex may cause side reactions, including the non-standard cleavage of the Rink amide linker [154].…”
Section: Immobilized Heterocyclic Peptide Conjugates As Ligandsmentioning
confidence: 99%
“…One specific example is the “Trojan Horse” approach to pathogen eradication, wherein a siderophore‐held iron atom can be actively taken up by bacteria, only to simultaneously deliver a tethered antibiotic structure, as pioneered by Miller and others [8,9] . Alternatively, many AMPs have been embellished with organometallic substituents including metallocenes, leading to improved activity [10–12] . Ferrocene in particular is inexpensive and known to display rather low toxicity (rat, oral LD 50 =1320 mg/kg); [13] accordingly, many ferrocene‐based antimicrobials have been reported and show improved efficacy as antimicrobial agents compared to their more traditional analogs [14–17] .…”
Section: Figurementioning
confidence: 99%
“…The inverse electron demand [4 + 2] pericyclic addition (Diels–Alder) between 1,2,4,5-tetrazines and electron-rich dienophiles provides a convenient method for generating new C–C bonds and heterocycles, and this technology has found applications in biological labeling. Recently, we and others reported that tetrazine metalation increases the rate as well as the selectivity of the dienophile addition compared to the nonmetalated tetrazine.…”
Section: Introductionmentioning
confidence: 99%